Evaluation of a fentanyl drug checking service for clients of a supervised injection facility, Vancouver, Canada - Mohammad Karamouzian; Carolyn Dohoo; Sara Forsting; Ryan McNeil; Thomas Kerr; Mark Lysyshyn (BMC, 2018)
Abstract Background British Columbia, Canada, is experiencing a public health emergency related to opioid overdoses driven by consumption of street drugs contaminated with illicitly manufactured fentanyl. This cross-sectional study evaluates a drug checking intervention for the clients of a supervised injection facility (SIF) in Vancouver. Methods Insite is a facility offering supervised injection services in Vancouver's Downtown East Side, a community with high levels of injection drug use and associated harms, including overdose deaths. During July 7, 2016, to June 21, 2017, Insite clients were offered an opportunity to check their drugs for fentanyl using a test strip designed to test urine for fentanyl. Results of the drug check were recorded along with information including the substance checked, whether the client intended to dispose of the drug or reduce the dose and whether they experienced an overdose. Logistic regression models were constructed to assess the associations between drug checking results and dose reduction or drug disposal. Crude odds ratios (OR) and 95% confidence intervals (CI) were reported. Results About 1% of the visits to Insite during the study resulted in a drug check. Out of 1411 drug checks conducted by clients, 1121 (79.8%) were positive for fentanyl. Although most tests were conducted post-consumption, following a positive pre-consumption drug check, 36.3% (n = 142) of participants reported planning to reduce their drug dose while only 11.4% (n = 50) planned to dispose of their drug. While the odds of intended dose reduction among those with a positive drug check was significantly higher than those with a negative result (OR = 9.36; 95% CI 4.25-20.65), no association was observed between drug check results and intended drug disposal (OR = 1.60; 95% CI 0.79-3.26). Among all participants, intended dose reduction was associated with significantly lower odds of overdose (OR = 0.41; 95% CI 0.18-0.89). Conclusions Although only a small proportion of visits resulted in a drug check, a high proportion (~ 80%) of the drugs checked were contaminated with fentanyl. Drug checking at harm reduction facilities such as SIFs might be a feasible intervention that could contribute to preventing overdoses in the context of the current overdose emergency.